Mixed methods analysis of eighteen worksite policies, programs, and environments for physical activity - J. Aaron Hipp; Elizabeth A. Dodson; Jung Ae Lee; Christine M. Marx; Lin Yang; Rachel G. Tabak; Christine Hoehner; Oriol Marquet; Ross C. Brownson (BMC, 2017)
Abstract Background This study examined whether specific worksite supports for physical activity (PA) were associated with total and domain-specific PA. Methods A cross-sectional, telephone-based study was conducted in four Missouri, USA, metropolitan areas in 2012 and 2013. Outcome variables included total PA and sub-domains (leisure, work, travel) measured using the International Physical Activity Questionnaire. Logistic regression determined odds of meeting PA recommendations, given access to and use of 18 unique PA worksite supports. A subsample of 119 participants also wore hip accelerometry for seven consecutive days and maintained a wear-time diary. Access to worksite supports were associated with odds of meeting objective moderate and vigorous (MV) PA above 150 min per week. Results Among 2013 survey participants, meeting PA recommendations while performing work-related tasks was significantly associated with several supports (e.g., walking maps, stair prompts), as was meeting recommendations during travel (e.g., flextime for PA, incentives for public transportation, walking/bicycling to work). Access to 11 worksite supports increased odds of meeting PA recommendations through leisure-time PA; five supports were associated with total PA. There were significant differences between access to and use of supports. Using objective MVPA, access to worksite challenges and bike storage were significantly associated with five and three times greater odds of meeting 150 min of MVPA per week, respectively. Conclusions Worksite wellness plans are increasing across the US and employers are eager for evidence-based supports for increasing PA. This study provides insights into the utility of multiple worksite supports for PA to increase odds that employees meet PA recommendations.